Metabolic Reprogramming of NK Cells by Black Phosphorus Quantum Dots Potentiates Cancer Immunotherapy - Lizhen He; Jianfu Zhao; Hongjun Li; Bin Xie; Ligeng Xu; Guanning Huang; Ting Liu; Zhen Gu; Tianfeng Chen (Advanced Science, 2023)
Abstract Low persistence, metabolic dysfunction in microenvironment, and tumor‐derived immunosuppression of Natural killer (NK) cells in patients are greatly limited the successful clinical application of NK cell‐based cancer immunotherapy. Interestingly, herein that human serum albumin‐encapsulated black phosphorus quantum dots (BPQDs@HSA) can effectively augment antitumor efficacy of clinical patients‐derived NK cell immunotherapy is found. As the donor of phosphate group, BPQDs@HSA binds with the protein of phosphatidylinositol 4‐phosphate 5‐kinase type‐1 gamma (PIP5K1A) and activates the downstream PI3K‐Akt and mTOR signaling pathways to reprogram cell metabolism of glycolysis and further promote the oxidative phosphorylation, sequentially maintains the cell viability and immunity of NK cells. And multiomics analysis is therefore conducted to reveal the underlying immunoregulation mechanisms, and that BPQDs@HSA can interact with the Toll‐like receptor (TLR) on the NK cell surface and increase the expression level of mTOR, and thus activate downstream NF‐κB signalling pathways to regulate cytokine secretion and enhance immune tumoricidal is found. BPQDs@HSA can also enhance immune surveillance, relieve immune suppression, and inhibit tumor immune escape. Collectively, this study not only demonstrates a successful strategy for nanomedicine‐potentiated immune‐cancer therapy, but also sheds light on the understanding of interface between nanomedicine and immune cells activation.